DIFFICULTIES IN IMPLEMENTING THE NATIONAL PLAN OF EQUATORIAL GUINEA FOR ATTRACTING FOREIGN CAPITAL - INVESTOR CONCERNS AND INTERCULTURAL GAPS - BUVILSKI, Eyal (Studia Universitatis Babes-Bolyai Studia Europaea, 2019)
This paper analyzes the difficulties of the government of Equatorial Guinea to fulfill an essential objective of its national development framework, i.e., the diversification of the economy through the private sector. This paper begins with a brief history of the country and its economy. The paper then moves to describe the efforts made by the government to attract foreign investors and outlines their concerns on the socio-political environment and business uncertainty. Equatorial Guinea, today one of Africa’s most important oil producers, used to be one of the world’s poorest countries with an economy mainly based on the growth of coffee and cocoa. In the mid-1990s, significant deposits of oil and gas were discovered, leading to a substantial economic change. In the following years, the government, supported by international organizations, decided to launch a national program. Its goals were building modern infrastructure, strengthening human capital, diversifying the economy through the private sector and maintaining efficient governance. As of today, attempts to attract foreign investors have not yet succeeded, and the economy continues to base on oil and gas revenues. The paper concludes by arguing that the way the locals perceive the governmental efforts, and the market conditions is entirely different from the way potential investors view it, and this gap must be bridged.